2018
DOI: 10.1016/j.amsu.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Mesh repair of paraumblical hernia, outcome of 58 cases

Abstract: BackgroundAccording to the literature, defects in para-umbilical hernias up to 2 cm in diameter could be sutured primarily. For defects larger than 2 cm in dimeters, mesh repair is recommended. The aim of this study is to evaluate the outcome of para-umbilical hernia repair with proline mesh regardless of its size.MethodsIn this retrospective study, patients with para-umbilical hernia, who were managed by onlay mesh placement were presented, and followed for 1–6 years. Several variables were studied including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Generally PUH and all other types of hernias are common in females than in males 3, 6,11 . The adipose tissue is different in both genders, which is considered to be the causative factor 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally PUH and all other types of hernias are common in females than in males 3, 6,11 . The adipose tissue is different in both genders, which is considered to be the causative factor 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that prosthetic repair for incarcerated PUH in the emergency settings have yielded good outcomes. [11][12][13][14][15][16] Pre-peritoneal prosthetic mesh was inserted successfully into 35 patients with strangulated groin hernias by Pans et al 12 Polypropylene meshes was used successfully by Wysocki et al to treat strangulated inguinal and incisional hernias. 14 Patients received Lichtenstein treatment for incarcerated groin hernias in a later report by the same group.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In the elective care of PUH, reoccurrence is expressively reduced for prosthetic repairs compared to traditional repairs, according to a number of recent studies. [8][9][10][11] This has prompted some researchers to argue that the best course of action for treating PUH may be prosthetic repair. 8,9 In the elective care of PUH, recurrence is suggestively reduced for prosthetic repairs compared to conventional repairs, according to a number of recent studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miniabdominoplasty is similar but with no umbilical reposition. Weakness of the linea Alba is common in obese multiparous women with pendulant abdomen, aggravated by incisional hernia especially, if developed in midline (6) .…”
Section: Introductionmentioning
confidence: 99%